Fungi of Great Salt Lake, Utah, USA: a spatial survey - Parrott, David L.; Baxter, Bonnie K. (Frontiers in Fungal Biology, 2024)
The natural system at Great Salt Lake, Utah, USA was augmented by the construction of a rock-filled railroad causeway in 1960, creating two lakes at one site. The north arm is sequestered from the mountain snowmelt inputs and thus became saturated with salts (250-340 g/L). The south arm is a flourishing ecosystem with moderate salinity (90-190 g/L) and a significant body of water for ten million birds on the avian flyways of the western US who engorge themselves on the large biomass of brine flies and shrimp. The sediments around the lake shores include calcium carbonate oolitic sand and clay, and further away from the saltwater margins, a zone with less saline soil. Here a small number of plants can thrive, including Salicornia and Sueda species. At the north arm at Rozel Point, halite crystals precipitate in the salt-saturated lake water, calcium sulfate precipitates to form gypsum crystals embedded in the clay, and high molecular weight asphalt seeps from the ground. It is an ecosystem with gradients and extremes, and fungi are up to the challenge. We have collected data on Great Salt Lake fungi from a variety of studies and present them here in a spatial survey. Combining knowledge of cultivation studies as well as environmental DNA work, we discuss the genera prevalent in and around this unique ecosystem. A wide diversity of taxa were found in multiple microniches of the lake, suggesting significant roles for these genera: Acremonium, Alternaria, Aspergillus, Cladosporium, Clydae, Coniochaeta, Cryptococcus, Malassezia, Nectria, Penicillium, Powellomyces, Rhizophlyctis, and Wallemia. Considering the species present and the features of Great Salt Lake as a terminal basin, we discuss of the possible roles of the fungi. These include not only nutrient cycling, toxin mediation, and predation for the ecosystem, but also roles that would enable other life to thrive in the water and on the shore. Many genera that we discovered may help other organisms in alleviating salinity stress, promoting growth, or affording protection from dehydration. The diverse taxa of Great Salt Lake fungi provide important benefits for the ecosystem.